2021
DOI: 10.21203/rs.3.rs-1043297/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Combined Supplementation of Probiotics and Enzymes Improves Performance and Regulates Rumen Microbiota in Fattening Goats

Abstract: Background: The aim of this study was to explore the effects of growth performance, slaughter performance, serum biochemical, immune and antioxidant indexes and rumen microflora fed with a basal diet (CON group), added B. subtilis and B. licheniformis (PRO group), supplemented with B. subtilis, B. licheniformis and enzyme preparations (COM group) on fattening goats.Methods: 39 male goats were randomly divided into 4 groups with 13 individuals in each group for feed period of 80 d. Goats were fed as follows: CO… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 38 publications
1
3
0
Order By: Relevance
“…The present study revealed that probiotics supplementation in Sunit sheep resulted in an increasing trend in final weight and carcass weight, along with a significant improvement in the LEA, which is consistent with previous research findings ( Lu et al, 2021 ). LEA, as a growth indicator, is highly positively correlated with meat production performance and lean meat percentage and is an important indicator for evaluating the carcass quality of domestic animals.…”
Section: Discussionsupporting
confidence: 93%
“…The present study revealed that probiotics supplementation in Sunit sheep resulted in an increasing trend in final weight and carcass weight, along with a significant improvement in the LEA, which is consistent with previous research findings ( Lu et al, 2021 ). LEA, as a growth indicator, is highly positively correlated with meat production performance and lean meat percentage and is an important indicator for evaluating the carcass quality of domestic animals.…”
Section: Discussionsupporting
confidence: 93%
“…The effectiveness of probiotics containing live bacterial cultures is associated with favorable metabolic changes in the digestive tract, better absorption of nutrients, increased body resistance to adverse conditions, and an antagonistic effect on pathogenic and opportunistic microflora. Some studies have shown that probiotics have a positive effect not only on the microbial ecosystem of the digestive tract, nutrient synthesis (Saha et al, 2018), they also lead to increases in carcass weight (Lu et al, 2021), muscle mass, and meat quality (Liu et al, 2022). In addition, as reported by Tekce et al (2021), supplementation with probiotics (Lacticasebacillus rhamnosus; Saccharomyces cerevisiae) for 2.5 months helped maintain microbial balance in the digestive tract of lambs at weaning.…”
Section: Discussionmentioning
confidence: 99%
“…Some probiotic strains can produce bacteriocins that act as tective agents against lipid oxidation and keep positive organoleptic attributes in me can be concluded that the use of probiotics improves the quality of meat. ↑ pre-slaughter weight ↑ rib tissue thickness (GR) [10] Abbreviations: ↑, increased; ↓, decreased; ~, not changed, CFU, colony-forming unit; LT, Longissimus thoracis; MAPK, mitogen-activated protein kinase; MyHC, myosin heavy chain; DM, dry matter; LAB, lactic acid bacteria.…”
Section: Effects Of Probiotic Supplementation On General Eating Quali...mentioning
confidence: 99%
“…Therefore, many investigators focused on antibiotics substitutes, namely feed additives or supplements as Microorganisms 2023, 11, 1652 2 of 14 probiotics (as single or mixed strains) to the animal feed [5,6]. Probiotics have been shown to have positive effects on the microbial ecosystem [7], nutrient synthesis [4,8], growth performance [9], carcass weight [10,11], muscle production and meat quality [3,[12][13][14], prevention of enteric diseases [15], and immunity [16]. A study showed that 2.5 months of dietary supplement of probiotics (Lacticasebacillus rhamnosus; Saccharomyces cerevisiae) could maintain microbial balance in the gastrointestinal tracts of weanling lambs [6].…”
Section: Introductionmentioning
confidence: 99%